Magnetic nanoparticle‐tethered Schiff base–palladium(II): Highly active and reusable heterogeneous catalyst for Suzuki–Miyaura cross‐coupling and reduction of nitroarenes in aqueous medium at room temperature. (31st January 2018) - Manjunatha, K.; Koley, Tuhin S.; Kandathil, Vishal; Dateer, Ramesh B.; Balakrishna, Geetha; Sasidhar, B. S.; Patil, Shivaputra A.; Patil, Siddappa A.
Abstract : As a continuation of our efforts to develop new heterogeneous nanomagnetic catalysts for greener reactions, we identified a Schiff base–palladium(II) complex anchored on magnetic nanoparticles (SB‐Pd@MNPs) as a highly active nanomagnetic catalyst for Suzuki–Miyaura cross‐coupling reactions between phenylboronic acid and aryl halides and for the reduction of nitroarenes using sodium borohydride in an aqueous medium at room temperature. The SB‐Pd@MNPs nanomagnetic catalyst shows notable advantages such as simplicity of operation, excellent yields, short reaction times, heterogeneous nature, easy magnetic work up and recyclability. Characterization of the synthesized SB‐Pd@MNPs nanomagnetic catalyst was performed with various physicochemical methods such as attenuated total reflectance infrared spectroscopy, UV–visible spectroscopy, inductively coupled plasma atomic emission spectroscopy, energy‐dispersive X‐ray spectroscopy, field‐emission scanning electron microscopy, transmission electron microscopy, powder X‐ray powder diffraction, thermogravimetric analysis and Brunauer–Emmett–Teller surface area analysis. Abstract : A Schiff base–palladium(II) complex anchored on magnetic nanoparticles (SB‐Pd@MNPs) as highly active nanomagnetic catalyst is reported for Suzuki‐Miyaura cross‐coupling between phenylboronic acid and a range of aryl halides and also for the reduction of nitroarenes using sodium borohydride in an eco‐friendly medium.